2020
DOI: 10.1029/2019gl086841
|View full text |Cite
|
Sign up to set email alerts
|

COSMIC‐2 Radio Occultation Constellation: First Results

Abstract: Initial data from the Formosa Satellite‐7/Constellation Observing System for Meteorology Ionosphere and Climate (FORMOSAT‐7/COSMIC‐2, hereafter C2), a recently launched equatorial constellation of six satellites carrying advanced radio occultation receivers, exhibit high signal‐to‐noise ratio, precision, and accuracy, and the ability to provide high vertical resolution profiles of bending angles and refractivity, which contain information on temperature and water vapor in the challenging tropical atmosphere. A… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
135
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 176 publications
(148 citation statements)
references
References 27 publications
12
135
0
1
Order By: Relevance
“…Besides the different data coverage, the FS7 satellites are capable of receiving signals from both the Global Positioning System (GPS) and Globalnaya Navigatsionnaya Sputnikovaya Sistema (GLONASS) [6]. FS7 satellites carry an antenna with a higher signal-to-noise ratio (SNR), which thus allows a deeper penetration of the ray into the lower troposphere and better detection of the atmospheric boundary layer (ABL) top and super-refraction (SR) on top of the ABL [7]. The six satellites of the FS7 constellation were successfully launched on 25 June 2019, and the FS7 neutral atmosphere data were officially released on 10 December 2019.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides the different data coverage, the FS7 satellites are capable of receiving signals from both the Global Positioning System (GPS) and Globalnaya Navigatsionnaya Sputnikovaya Sistema (GLONASS) [6]. FS7 satellites carry an antenna with a higher signal-to-noise ratio (SNR), which thus allows a deeper penetration of the ray into the lower troposphere and better detection of the atmospheric boundary layer (ABL) top and super-refraction (SR) on top of the ABL [7]. The six satellites of the FS7 constellation were successfully launched on 25 June 2019, and the FS7 neutral atmosphere data were officially released on 10 December 2019.…”
Section: Introductionmentioning
confidence: 99%
“…Applications of FS3 RO data to many aspects of weather prediction and analysis can be found in a number of literatures and have been documented in detail by [1]. The authors of [7] compared the FS7 RO data with different datasets and showed that the FS7 data possess high accuracy and precision. For example, they compared the FS7 RO dry products (bending angle and refractivity) with the European Centre for Medium-Range Weather Forecasts (ECMWF) short-term forecasts and showed that the RO data are quite consistent, with very small biases between 6 and 40 km.…”
Section: Introductionmentioning
confidence: 99%
“…4 | EVALUATION OF COSMIC-2 IMPACTS ON NWP Schreiner et al (2020) have already demonstrated the quality of the COSMIC-2 bending angle profiles by comparing with NWP analyses and reanalyzes. We obtain similar results in these kind of comparisons, but they will not be reproduced here.…”
Section: Assumed Bending Angle Uncertaintymentioning
confidence: 99%
“…COSMIC-2 provides measurements made with GPS and GLONASS signals for the first time. Schreiner et al (2020) have presented the first estimates for the precision and accuracy of the GPS and GLONASS COSMIC-2 data, by computing differences of nearby COSMIC-2 profiles, and comparing them with both NWP short-range forecasts and reanalyzes. They emphasize that an important aim of this mission is to improve the GNSS-RO measurement quality in the troposphere, with the use of an advanced Tri-GNSS Radio Occultation System (TGRS) instrument.…”
Section: Introductionmentioning
confidence: 99%
“…RS stations are distributed more densely in East Asia, Europe, and North America than elsewhere. Satellite missions, such as the Constellation Observing System for Meteorology, Ionosphere, and Climate-1, -2 [5][6][7], provide nearly evenly and densely distributed RO profiles over the world, making up for the lack of conventional observations over the ocean.…”
Section: Introductionmentioning
confidence: 99%